[PP.12.05] THE ROLE OF PERIVASCULAR ADIPOSE TISSUE AND INSULIN IN REGULATING MICROVASCULAR TONE WITHIN SKELETAL MUSCLE RESISTANCE ARTERIES. (September 2016) - Clark, B.; Withers, S.B.; Heagerty, A.M.
Abstract : Objective: Microvascular tone of resistance arteries determines insulin-sensitivity by controlling downstream nutritive blood flow to skeletal muscle, the predominant site of insulin-induced glucose uptake. Surrounding most blood vessels, perivascular adipose tissue (PVAT) exerts a relaxant 'anti-contractile' effect upon the vasculature. Few studies on skeletal muscle resistance arteries have investigated this effect and the role of insulin on vascular tone. We therefore aimed to address these issues through establishing a novel in vitro model. Design and method: Vascular contractility of arterial segments, with (+) or without (-) PVAT, from hindlimb skeletal muscle resistance arteries of healthy male Wistar rats was assessed by wire myography. Viable vessels achieved tensions =>0.3mN/mm when challenged with 60 mM high-K+ physiological saline solution (KPSS). Arterial segments were subsequently pre-constricted with noradrenaline (30 μM) and endothelial function was confirmed by vasodilation (=>25% reduction of noradrenaline-induced tension) in response to carbachol (30 μM, ∼10 min). Vessels were then challenged with either serotonin or noradrenaline (−8 to −4.5 log10 M), and the effects of insulin (2 nM, 30 min pre-incubation) were investigated on the noradrenaline-induced dose-response. Responses were normalised to post-dose-response KPSS-induced constrictions. Statistical analyses were performed via two-way ANOVA with Bonferroni post-hoc analysis. Results: Neither endothelium nor PVAT affected basal vasoreactivity, as KPSS-induced constrictions were unchanged. PVAT exerted an endothelium-independent anti-contractile effect in response to serotonin (-PVAT: n = 8; +PVAT: n = 8; P < 0.0001), which was potentiated by endothelium (-Endothelium: n = 8; +Endothelium: n = 3; P < 0.0001). Contrastingly, endothelium but not PVAT exerted anti-contractility in response to noradrenaline (-Endothelium n = 8, +Endothelium n = 10, P < 0.0001). Following insulin pre-incubation, noradrenaline induced either PVAT-mediated anti-contractility or pro-contractility depending upon the absence (Noradrenaline: n = 8; Insulin: n = 4; P = 0.009) or presence (Noradrenaline: n = 10; Insulin: n = 2; P = 0.0007) of endothelium. Conclusions: Serotonergic and adrenergic stimulation elicit anti-contractile responses through PVAT and the endothelium, respectively. Consistent with previous studies, insulin has a vaso-modulatory role, acting as both a vasodilator and vasoconstrictor through different mechanisms not investigated herein. Future refinement of this model should allow for the vasoactive effects of insulin to be investigated in relation to obesity-induced insulin-resistance and the development of the devastatingly prevalent metabolic syndrome.